A monograph on agriculture and food policies in Morocco : 1969-1991 - Driouchi A.; Laraki K. (Food and agricultural policies in the Middle East and North Africa: Egypt, Lebanon, Morocco, Sudan, Tunisia, Turkey, 1994)
This monograph on agricultural and food policies in Morocco discusses the effects of agricultural policy and the main forces governing public intervention and market forces during the period 1969-1991. The overall economic environment is described, and certain features of supply, demand, marketing and trade of agricultural food and non-food items are quantified, in order to identify and evaluate the economic factors underlying trends and directions in production, consumption and prices. The study period covers different agricultural and food policy regimes, although it was difficult to analyze subperiods coinciding with socioeconomic plans or specific policy sets. The usual procedure was to consider the overall study period and then to compare the government interventionist era of the 1970s and early 1980s with the post-1983 period of structural adjustment policies. Little aggregate data was available for the second period, during which time major changes took place in the agricultural and food economy. The results obtained have been used primarily to recommend future directions for economic research. Medium- and long-term research topics are proposed as useful means to evaluate different economic scenarios and to suggest appropriate adjustment actions.
Workshop on Food and Agricultural Policies in the Middle East and North Africa, 1993/07/05-07, Tunis (Tunisia)